Portuguese migration to the Canary Islands: An analysis based on surnames - Román Busto, Jorge (2012)
As a part of a wider analysis of population and genetic exchange between Spain and Portugal, the long term pattern of Portuguese immigration to the Canary Islands was studied by means of the frequency of Portuguese surnames. A database of 1,995,833 individuals was obtained from the Spanish National Statistics Institute (2006). Among the 826 most frequent surnames to appear, 79 surnames of Portuguese origin were selected. The distribution of these surnames by municipalities and islands, the Fisher index of diversity, and the Lasker inter-population relationship coefficients Rij were considered. These coefficients were inter-correlated and correlated with other variables that could have influenced the distribution of surnames. From the observed distribution of the frequency of surnames, a non-random migration pattern conditioned by economic factors was found. The greatest diversity of surnames existed in cane cultivating areas after the first arrival of Portuguese immigrants. A later dispersion of surnames among islands was correlated with the inter-island geographic distances. In some islands the arrival of new immigrants continued due to their strategic location within the Canary archipelago. The Canary Islands reveal a high frequency and diversity of Portuguese surnames. The results also prove a heterogeneous distribution of these surnames throughout the archipelago. In contrast to the Portuguese archipelagos, some Canary localities have received immigrants continuously because of their economic importance in sugar cane cultivation and strategic geographic location on the maritime routes to Africa and America.